89.0k views
0 votes
Stuck on this one .......

Stuck on this one .......-example-1
User Sludge
by
4.4k points

2 Answers

2 votes

Answer:

Exponent Product Rule

Explanation:

Exponent multiplication: (a^b)(a^c)= a^(b+c)

t^3=(t^2)t

Because t=t^1, we have

t^2+t^1=t^3

This can be shown by the Exponent Product Rule

User Lok
by
5.3k points
3 votes

Answer: t²⁺¹

Explanation:

The law of exponents states that when multiplying terms with the same base, you ADD the exponents. Note that "t" has an exponent of 1.

t³ = (t²)t¹ = t²⁺¹

I hope this is what you were looking for.

User Qinmiao
by
4.8k points